2002
DOI: 10.1016/s1047-2797(01)00282-4
|View full text |Cite
|
Sign up to set email alerts
|

Quitting Smoking May Restore Hematological Characteristics within Five Years

Abstract: PURPOSE:To describe the cross-sectional association of counts of total and subtypes of leukocytes, platelets, and selected characteristics of red blood cells with intensity of cigarette smoking and smoking cessation. METHODS:The study population consisted of 16,254 men and women 20-70 years of age who participated in the Dutch European Prospective Investigation into Cancer and nutrition (EPIC) subcohort, 1995-1997. Linear regression analysis was performed, for both sexes separately, to study the relation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 35 publications
7
62
0
2
Order By: Relevance
“…In our series, men smoking >10 cigarettes/day had a 1.4% increase in haemoglobin compared to non-smokers, whereas in women, the increase was on the average 3.5%, which is in accordance with the carboxyhaemoglobin levels of 3-6% reported in smokers [14,17]. "Normalization" of haemoglobin after smoking cessation has likewise been reported in humans [7,8].…”
Section: Smoking and Alcohol Vs Serum Ferritinsupporting
confidence: 90%
See 2 more Smart Citations
“…In our series, men smoking >10 cigarettes/day had a 1.4% increase in haemoglobin compared to non-smokers, whereas in women, the increase was on the average 3.5%, which is in accordance with the carboxyhaemoglobin levels of 3-6% reported in smokers [14,17]. "Normalization" of haemoglobin after smoking cessation has likewise been reported in humans [7,8].…”
Section: Smoking and Alcohol Vs Serum Ferritinsupporting
confidence: 90%
“…Tsang et al [6] examined 3,654 Australian subjects 49-97 years of age and stated that smoking and alcohol influenced the reference range but did not report any specific details. In a Dutch cohort study of 16,254 subjects 20-70 years of age, Van Tiel et al [8] found higher haemoglobin in smokers than in non-smokers of both genders. Skjelbakken et al [7] examined a cohort of 4,159 Norwegian men 20-49 years of age at baseline and 20 years later.…”
Section: Smoking and Alcohol Vs Serum Ferritinmentioning
confidence: 96%
See 1 more Smart Citation
“…7, 48 We did not find strong evidence to support this among any of our biomarkers. It may be that our follow-up period was not long enough to detect these changes, as some of them were observed at 6 months postcessation.…”
Section: Discussionmentioning
confidence: 58%
“…A cigarette smoke contains over 4000 chemicals [2] and a cigarette smoker is exposed to harmful substances including nicotine, free radicals, carbon monoxide, and other gaseous products [3]. It is well known that smokers have higher risk for cardiovascular diseases, hypertension, inflammation, stroke, clotting disorder, and respiratory disease [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%